PERAN GURU BK DALAM MENGOPTIMALKAN PRESTASI BELAJAR ANAK HIPERAKTIF - Devia Aprilianti; Yahdinil Firda Nadhirah (STKIP Subang, 2025)
This study aims to describe in depth the inclusive education services for Students with Special Needs (ABK) with Attention Deficit Hyperactivity Disorder (ADHD), focusing on the crucial role of the School Counselor (Guru Bimbingan dan Konseling - BK) in optimizing students' academic achievement. The research used a descriptive qualitative approach with a literature review, and collected data through observation, interviews, and documentation at a special needs school, SKH Negeri 01 Kabupaten Tangerang, with the subjects being the School Counselor and the Vice Principal, analyzed using the Miles and Huberman (2014) model. The results of the theoretical review and field findings confirm that ADHD is a neurodevelopmental disorder characterized by executive function deficits, social difficulties (peer rejection), and specific learning challenges (APA, 2000/2013), thus requiring holistic and inclusive services. The inclusive approach is proven effective in increasing the engagement of students with ADHD, especially through curriculum adaptations adhering to the principles of the Salamanca Statement (1994) and effective classroom management that demands high competence from the classroom teacher (Wijaya, 2019). In this context, the School Counselor plays a central role as an agent of Comprehensive School Counseling (DuPaul et al., 1998), by providing education, facilitating collaboration, applying Cognitive Behavioral Interventions (CBI) to improve Self-Regulation (Pfiffner et al., 1998), and acting as an advocate for the fulfillment of students' rights. Close collaboration among the School Counselor, classroom teachers, and parents is the main determinant of the consistency and success of intervention strategies. Overall, the study concludes that despite facing complex challenges due to ADHD, with integrated and competent inclusive support and services, children with ADHD have an equal opportunity to enhance their engagement and achieve optimal academic achievement.